Severe recalcitrant hidradenitis suppurativa in a 2‐year‐old boy with partial trisomy 13. Issue 3 (1st March 2022) - Keyes, Emily; Larijani, Mary; Castelo‐Soccio, Leslie; Treat, James R.
Abstract: We report the case of a 2‐year‐old boy with mosaic trisomy 13 and immunodeficiency who developed severe hidradenitis suppurativa beginning at the age of 18 months. Unresponsive to standard therapies, he exhibited a partial response to immunoglobulin replacement therapy.